Biomechanical analysis of the moment about the center of mass during the downswing phase in women's driver shot - Okamoto, A. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to investigate the moment about the center of mass (CM) acting on the golfer-club system during the downswing phase in women`s driver shots. Fourteen female golfers volunteered as subjects. The maximum clubhead speed, angular momentum ot the thorax and moment about the CM were calculated. There was a strong significant correlation between the frontal-plane moment about the CM and the maximum clubhead speed (p<0.01). At the same time, there was a significant correlation between the frontal-plane moment about the CM and angular momentum of the thorax about the Z-axis (p<0.05). In conclusion, in order to get higher clubhead speed it is important to generate the larger frontal-plane moment about the CM and to transfer the momentum generated from the body to the clubhead.